If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 9 = 15x Reorder the terms: 9 + 6x = 15x Solving 9 + 6x = 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 9 + 6x + -15x = 15x + -15x Combine like terms: 6x + -15x = -9x 9 + -9x = 15x + -15x Combine like terms: 15x + -15x = 0 9 + -9x = 0 Add '-9' to each side of the equation. 9 + -9 + -9x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -9x = 0 + -9 -9x = 0 + -9 Combine like terms: 0 + -9 = -9 -9x = -9 Divide each side by '-9'. x = 1 Simplifying x = 1
| n^2-3n-40= | | 9x-14=6x-13 | | -5n+3n=4n-5n | | x^2=x+25 | | y=17x+544 | | 7x+10=27 | | 6w+5-5w=8-3 | | 6=2x+6(x+5) | | -112=7j | | -4(x+2)=6x+10x+2 | | (x+5)2-(x+5)(x-5)= | | -5r-2r=-15-8r+3+7 | | 4x-5=4x+9 | | -3w+8(w-4)=-2 | | 7-2b=19 | | 75=10x-5 | | 1+b=-18-4 | | 27+3x=111 | | -13m+7m=19-73 | | 5x+11=12x-10 | | 10x-2-6x=3y-2+y | | 3x+15+9x+21=180 | | -11x-20=10+40 | | 6y+12=3t+14 | | 6(v+4)-4v=4 | | 14s+2.00=20s+1.50 | | 15Z-32=13 | | -9=-5+t | | x=3+2i | | 14s+2=20s+150 | | -9=5+t | | 8x-7=6x+23 |